The Soviet Price Reform Discussion - Bornstein, Morris (Quarterly Journal of Economics, 1964)
I. Background of the discussion, 16. — II. Criticisms of present industrial wholesale prices, 18; relationship of price to “value,” 20; relative prices and choice, 21; control and evaluation of enterprise performance, 22; measurement of macroeconomic relationships, 23. — III. Reform proposals, 23; the traditionalist school, 24; the surplus product markup schools, 28; the opportunity cost school, 36. — IV. Conclusion, 45.